Performance-oriented Architecture and the Spatial and Material Organisation Complex. Rethinking the Definition, Role and Performative Capacity of the Spatial and Material Boundaries of the Built Environment - Hensel, Michael Ulrich (FormAkademisk, 2011)
This article is based on the proposition that performance-oriented design is characterised by four domains of ‘active agency’: the human subject, the spatial and material organisation complex and the environment (Hensel, 2010). While these four domains are seen to be interdependent and interacting with one another, it is nevertheless necessary to examine each in its own right. However, the spatial and material organisation complex contains both the spatial and material domains, which are interdependent to such a degree that these need to be examined in relation to one another and also in relation to the specific environment they are set within and interacting with. To explore this combined domain within the context of performance-oriented design is the aim of this article, in particularly in relation to the question of the definition and performative capacity of spatial and material boundaries. The various sections are accompanied by research by design efforts undertaken in specified academic contexts, which are intended as examples of modes and areas of inquiry relative to the purpose of this article.